Synthesis and Evaluation of Imidazolium Based Ionic liquIds as Corrosion Inhibitor for Mild Steel in Hydrochloric Acid Medium: Electrochemical, Thermodynamic and Theoretical Studies - N. Subasree; Renjith Sasimohanan Pillai; J. Arockia Selvi (Research Aspects in Chemical and Materials Sciences Vol. 3, 2022)
Iimidazolium based ionic liquids (ILs) such as, 3-hexadecyl-1-methyl-1H-imidazol-3-ium bromide [C16M1Im] [Br] and 3-hexadecyl-1,2-dimethyl-1H-imidazol-3-ium bromide [C16M2Im] [Br] were synthesized and evaluated for corrosion resistance on mild steel in 1M HCl solution by weight loss and electrochemical methods. The results revealed that the inhibition efficiency, enhanced with a rise in the concentration of inhibitor. Additionally, [C16M2Im] [Br] demonstrated greater inhibitory efficacy than [C16M1Im] [Br] due to the addition of more alkyl substituents. According to a polarisation investigation, the utilised inhibitors exhibit mixed-type behaviour but primarily have anodic inhibitory effects. The Langmuir adsorption isotherm is followed by the inhibitors adsorbed on the mild steel surface. Atomic force microscopy (AFM) and scanning electron microscopy (SEM) with EDAX analysis were used to analyse the surface topography. The development of the Fe-inhibitor complex on the surface of mild steel has been verified by UV-visible spectroscopy. Quantum chemical parameters calculated for [C16M1Im] [Br] and [C16M2Im] [Br] support the results obtained from experimental methods.